Assessment of mental health conditions among working class people during COVID-19: insights from Dhaka South City, Bangladesh - Al Jamal Mustafa Shindaini; Afroza Irin; Mohammad Mahbubur Rahman; Sajia Afrin (Intelektual Pustaka Media Utama, 2022)
The recent coronavirus disease 2019 (COVID-19) virus caused unprecedented vulnerabilities in the physical and mental health conditions of people across the world. This research explored the effect of COVID-19 on the mental health, sleeping patterns and professional atmosphere of the working people of Dhaka South City (DSC) in Bangladesh. We applied a range of tools of quantitative method to carry out the present study. The data were collected from purposively selected 139 respondents from DSC. A structured questionnaire was prepared and disseminated among the sampled respondents through online platforms in October 2020. Employing the depression anxiety stress scale (DASS) 21 scale, the study revealed that depression (82.7%), anxiety (87.8%), stress (77.7%) and sleep disturbance (56.1%) occurred due to the COVID-19 pandemic in the study area. In addition, the paper found that respondents faced difficulty concentrating on work (p<0.05), felt workload pressure, and experienced shaky mental conditions (p<0.05) accompanied by mild to extremely severe conditions of depression, stress, and anxiety. Statistical analysis pearson Chi-square test showed that socio-demographic aspects and COVID-19 factors significantly impacted mental health conditions among the respondents. This research recommends providing low-intensity psychological interventions and mental health strategies are needed to lessen sufferings for the target population.